2013
DOI: 10.1155/2013/940438
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angiitis of the Central Nervous System: A Report of Three Cases from a Single Colombian Center

Abstract: The primary angiitis of the central nervous system (PACNS) is an entity with a very low incidence and prevalence. It is not clear why the inflammatory process of this entity is limited to the cerebral vasculature without systemic manifestations. Its clinical manifestations are very heterogeneous and make clinical diagnosis difficult. In most cases, a brain biopsy is required. Only the clinical suspicion and the ability to recognize the possible clinical and imagenological patterns of presentation make an accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Unlike our case, segmental granulomatous changes typical of granulomatous angiitis of the CNS (GACNS), was not observed [5,6]. The case by Ho et al reported presence of granulomatous findings supporting histopathological criteria for PACNS/GACNS [3].…”
Section: Accepted Manuscriptsupporting
confidence: 49%
“…Unlike our case, segmental granulomatous changes typical of granulomatous angiitis of the CNS (GACNS), was not observed [5,6]. The case by Ho et al reported presence of granulomatous findings supporting histopathological criteria for PACNS/GACNS [3].…”
Section: Accepted Manuscriptsupporting
confidence: 49%
“…A total of 46 eligible articles (eFigure 1, links.lww.com/NXI/A629), comprising 911 unique patients diagnosed with PACNS, were included in the meta-analysis: 372 biopsy-confirmed, 394 angiogram-confirmed, and 145 patients who could not be assigned to a diagnostic procedure (eTable 1, links.lww.com/NXI/A628). 3,9-13,14-53 A majority of the included studies (n = 29, 63%) reported cases from Western Europe and the United States between 1988 and 2018. The median follow-up duration ranged from 0.75 to 61.2 months.…”
Section: Resultsmentioning
confidence: 99%
“…Salvarani et al report a median dose of 1 g and Oon et al a median dose of 800–1000 mg/mo 11 , 35 Oral cyclophosphamide was administered in 9 of 30 studies and was given daily with a median starting dose of 150 mg/day and a median treatment duration of 7 months, with a median starting dose of 100 mg/day and a median treatment duration of 10 months, or with 2 mg/kg/day and a treatment duration of 6 months. 11 , 25 , 34 , 43 , 49 , 52 Five studies did not report whether glucocorticoids or cyclophosphamide were given orally or IV. 3 , 37 , 38 , 47 , 48 Other induction treatments include cyclophosphamide alone or combinations of glucocorticoids with azathioprine, mycophenolate mofetil, rituximab, or methotrexate.…”
Section: Resultsmentioning
confidence: 99%
“…The symptomatology in those with predominant involvement of small vessels includes seizures, dyskinesia, and altered consciousness, while the medium/large vessel variant commonly generates focal symptoms 8 . Sartiet al 3 Angiographic MRI abnormalities are present in 90% of cases, mainly ischemic ones in 59% 9,10 . Multiple cortical and subcortical infarcts (63%) are often detected bilaterally (83%) 1,11 , as in this report in which there were lesions in both cerebellar hemispheres.…”
Section: Discussionmentioning
confidence: 98%